Workshops with refugees: Special experiences from the work with elderly people - Kostić Miomira P.; Đorđević Radmila (Temida)
The authors explain the phenomenon of refuge as a form of experience which differentiate refugees from indigenous population. They explore changes in number and geographical distribution of refugees in Serbia and Montenegro. Also, the method of work and goals of the humanitarian organization "Hi Neighbor" are elaborated. The paper is focused on the workshops with elderly people. One of the workshop activities is drawing on the topic "My personal space". In the pictures drawn by refugees the readiness for establishment of "life line", interrupted "somewhere", by the war and refuge, is pronounced.